Key findings to expedite the diagnosis of hyper‐IgE syndromes in infants and young children. Issue 2 (26th January 2016) - Hagl, Beate; Heinz, Valerie; Schlesinger, Anne; Spielberger, Benedikt D.; Sawalle‐Belohradsky, Julie; Senn‐Rauh, Monika; Magg, Thomas; Boos, Annette C.; Hönig, Manfred; Schwarz, Klaus; Dückers, Gregor; von Bernuth, Horst; et al.
Abstract: Background: Hyper‐IgE syndromes (HIES) are primary immunodeficiency disorders characterized by elevated serum IgE, eczema, and recurrent infections. Despite the availability of confirmatory molecular diagnosis of several distinct HIES entities, the differentiation of HIES particularly from severe forms of atopic dermatitis remains a challenge. The two most common forms of HIES are caused by mutations in the genes STAT3 and DOCK8 . Methods: Here, we assess the clinical and immunologic phenotype of DOCK8‐ and STAT3‐HIES patients including the cell activation, proliferation, and cytokine release after stimulation. Results: Existing HIES scoring systems are helpful to identify HIES patients. However, those scores may fail in infants and young children due to the age‐related lack of clinical symptoms. Furthermore, our long‐term observations showed a striking variation of laboratory results over time in the individual patient. Reduced memory B‐cell counts in concert with low specific antibody production are the most consistent findings likely contributing to the high susceptibility to bacterial and fungal infection. In DOCK8‐HIES, T‐cell lymphopenia and low IFN‐gamma secretion after stimulation were common, likely promoting viral infections. In contrast to STAT3‐HIES, DOCK8‐HIES patients showed more severe inflammation with regard to allergic manifestations, elevated activation markers (HLA‐DR, CD69, CD86, and CD154), and significantly increased inflammatory cytokines (IL1‐beta, IL4, IL6, and IFN‐gamma). Conclusion: Differentiating HIES from other diseases such as atopic dermatitis early in life is essential for patients because treatment modalities differ. To expedite the diagnosis process, we propose here a diagnostic workflow. Abstract :